Analysis Of the Existing Healthcare Signages for The Elderly in Kota Kinabalu: For Effective Healthcare Signages - Chou En-I; Mohamad Puad Bebit (Penerbit UMS, 2021)
Signage is a kind of graphic design, which can be in the form of symbols and words, especially for conveying directions or warning information. Malaysia will become an ageing country by year 2030. The difference between ageing and diseases lies in its ubiquity. Diseases may be deterred, cured and removed but ageing is a natural process that everyone goes through. It cannot be avoided by anyone. As people age, they succumb more easily to illness and diseases. Therefore, the elderly tends to go to hospitals more often than other age groups. Hospitals have a complex setting and environment which may cause confusion for visitors with a 30 to 40 per cent rate of visitors getting lost. At present, Malaysia has carried out a large number of research related to the elderly, but the information related to the use of healthcare signage in Kota Kinabalu and the perception of the elderly is limited, so it will be very important to study ways to improve the level of healthcare signage. This paper discusses the physiological characteristics of the elderly by consulting existing literatures, provides suggestions to improve the designs causing an effective display of healthcare signage and also analyses the existing healthcare signage in Kota Kinabalu. The data collection qualitative research method used in this study is walk-through observation and semi-structured interviews from the main, public and private, hospitals in Kota Kinabalu, Malaysia. Making it helpful to upgrade the existing construction of healthcare way-finding signage for the elderly and help the elderly to obtain safe, smooth and independent medical services.